Clinical Experience with Daptomycin in Pediatrics. Issue 1 (6th January 2017) - Namtu, Katie C.; Crain, Julianna C.; Messina, Allison F.; Dumois, Juan A.; Berman, David M.
Abstract : Introduction: The management of gram‐positive infections has been complicated in recent years by the emergence of antimicrobial resistance, leaving fewer options for therapy. Daptomycin is a lipopeptide antibiotic used for the systemic treatment of gram‐positive infections. It has a distinct mechanism of action and a favorable side effect profile, and it requires once/day dosing. Unfortunately, there is a paucity of safety, efficacy, and pharmacokinetic data in neonatal and pediatric patients. The objective of this study was to review our experience with daptomycin use for the treatment of gram‐positive infections in these patient populations. Methods: We conducted a retrospective analysis of electronic medical records of hospitalized children who received daptomycin between October 2008 and June 2014 for the treatment of proven gram‐positive infections. Results: Of the 146 patients who received at least 3 days of daptomycin therapy, 109 patients had a proven gram‐positive infection and were included for further analysis. Of the 109 patients, 71 were males (65%) and the median age was 12 years (range: 2.5 mo to 24 yrs). The median duration of therapy was 12 days (range: 3–121 days; mean = 16 days). Catheter‐related bloodstream infections were the most common type of infections (n=81 patients) in those receiving daptomycin treatment. One hundred seven patients (98%) had documented improvement and resolution at the time of hospital discharge. One hundred four patients (95%) had a baseline creatine phosphokinase (CPK) level obtained. Of these 104 patients, 48 (46%) had at least one follow‐up CPK level after the start of therapy. Three patients' charts showed laboratory evidence of elevated CPK values. Conclusions: The majority of patients demonstrated clinical improvement after receiving daptomycin as primary therapy for proven gram‐positive infections. Larger randomized controlled trials focusing on safety and efficacy are necessary to assess these outcomes with daptomycin use in the pediatric population.